Implementation of Business Process Reengineering To Minimize Customer Complaints - Muhammad Dzul Fikry; Indri Sudanawati Rozas; Faris Muslihul Amin (PT. Publikasiku Academic Solution, 2023)
Service in an organization is highly correlated with the level of customer satisfaction with the quality of service provided. From this activity, improvements will be made to the Business Processing Reengineering method so that the business process can run properly and efficiently. To test whether it is true that the Business Process Reengineering (BPR) approach has been able to minimize customer complaints, in this case, PDAM Giri Tirta Gresik will carry out an identification and analysis stage first on any problems. Based on the existing problems, the focus of this research was emphasized on the service process to fulfill clean water in Gresik Regency, especially in the reengineering process for new installations. A comparison of new installation business processes before and after the Business Process Reengineering, namely the percentage of throughput efficiency tests of 94.44% from 73.99% of ongoing business processes and provides the final simulation results in the form of BPMN notation which takes maximum time. which is obtained in 24 days 2 hours 20 minutes from 26 days 16 hours 5 minutes in the new installation process.